2005
DOI: 10.1039/b502088n
|View full text |Cite
|
Sign up to set email alerts
|

Feedback dynamics and cell function: Why systems biology is called Systems Biology

Abstract: A new paradigm, like Systems Biology, should challenge the way research has been conducted previously. This Opinion article aims to present Systems Biology, not as the application of engineering principles to biology but as a merger of systems- and control theory with molecular- and cell biology. In our view, the central dogma of Systems Biology is that it is system dynamics that gives rise to the functioning and function of cells. The concepts of feedback regulation and control of pathways and the coordinatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
65
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 86 publications
(65 citation statements)
references
References 3 publications
0
65
0
Order By: Relevance
“…A standard approach to the dynamics of cell signalling networks is the framework of chemical kinetics. Within this framework enzyme kinetic reaction (1) is represented as a system of four coupled ordinary differential equations [11,22] …”
Section: Assumptions Of the Studymentioning
confidence: 99%
“…A standard approach to the dynamics of cell signalling networks is the framework of chemical kinetics. Within this framework enzyme kinetic reaction (1) is represented as a system of four coupled ordinary differential equations [11,22] …”
Section: Assumptions Of the Studymentioning
confidence: 99%
“…In this approach, the focus is on quantitative analysis of the interactions between individual components in a biological system and how these interactions evolve with time. A recurrent theme in this field is the importance of feedback loops in generating spatiotemporal patterns (5). Pioneering work in the study of oocyte maturation, for instance, has demonstrated the critical role of positive feedback in cell fate decision (6).…”
mentioning
confidence: 99%
“…Such regulatory networks often have downstream components that provide input to components that act earlier in a pathway, creating feedback loops (Langlois et al 1995) These feedback loops have the potential to greatly alter the properties of a pathway and how it responds to stimuli (Aronson et al 1994;Bliss et al 1982;Chen and Tan 2000;Lauffenburger 2001;Wolkenhauer and Mesarovic 2005). Positive and negative feedback loops around MAPK (Mitogenactivated protein kinase) cascades have been a topic of interest in biological literature.…”
Section: Introductionmentioning
confidence: 99%
“…For example, in (Ferrell and Machleder 1998), one finds the study of positive feedback (on Mos by ERK) in the context of progesterone-induced oocyte maturation in frogs. In another example, Kholodenko (2000) and Wolkenhauer and Mesarovic (2005) looked at negative feedback, also in an ERK cascade, but affecting upstream proteins. JNK activation is an autocatalytic, in his work Bagowski and Ferrell (2001) has proposed two possible feedbacks, one from MAPK to MAPKK (Mitogen-activated protein kinase kinase) and the other from MAPKK to MAP-KKK(Mitogen-activated protein kinase kinase kinase) in JNK cascade in xenopus oocytes.…”
Section: Introductionmentioning
confidence: 99%